Religion at Work in Bioethics and Biopolicy: Christian Bioethicists, Secular Language, Suspicious Orthodoxy. Issue 2 (2nd April 2021) - Blackford, Russell; Schüklenk, Udo
Abstract: The proper role, if any, for religion-based arguments is a live and sometimes heated issue within the field of bioethics. The issue attracts heat primarily because bioethical analyses influence the outcomes of controversial court cases and help shape legislation in sensitive biopolicy areas. A problem for religious bioethicists who seek to influence biopolicy is that there is now widespread academic and public acceptance, at least within liberal democracies, that the state should not base its policies on any particular religion's metaphysical claims or esoteric moral system. In response, bioethicists motivated by religious concerns have adopted two identifiable strategies. Sometimes they rely on slippery-slope arguments that, sometimes at least, have empirically testable premises. A more questionable response is the manipulation and misuse of secular-sounding moral language, such as references to "human dignity, " and the plights of groups of people labeled "vulnerable."